Voluntary Disclosure of Greenhouse Gas Emissions: Contrasting the Carbon Disclosure Project and Corporate Reports - Depoers, Florence (Journal of business ethics, 2016)
As global warming continues to attract growing levels of attention, various stakeholders (states, general public, investors, and lobbyists) have put climate change on corporate agendas and expect firms to disclose relevant greenhouse gas (GHG) information. In this paper, we investigate the consistency of the GHG information voluntarily disclosed by French listed firms through two different communication channels: corporate reports (CR) and the Carbon Disclosure Project (CDP). More precisely, we contrast the amounts of GHG emissions reported and the methodological explanations provided (named ‘traceability’) in each channel. Consistent with a stakeholder theory perspective, we find that GHG amounts are significantly lower in the CR than in the CDP. We also find that firms increase the CR figures’ traceability when there is a discrepancy between disclosures in the two channels. We suggest that the aim of this greater traceability is to enhance information credibility across the different channels used.